(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This academic article aims to study about leadership according to the Buddhist concepts which can be said that Buddhist leadership is a process of influence in which leaders on individuals or groups lead to the achievement of goals that all are willing and mutually satisfied by interacting, conveying ideas into the continued action of A process that relates and influences between a leader, followers, and a situation or a task using Buddhist concepts as the main leading. (SamritKangpeng, 2019). So a really great leader is who can put truth, righteousness as a reference that allows people to join forces in the creation of life and society without the need for greed or anger as a stimulus. (Phraphromkhunaphorn, P.A.Payutto, 2005). Leadership individuals must be willing to tolerate problems arising from the performance of their assigned duties to the best of their ability leading to the promotion of better management and sustainability which must consist of virtues in self-management, namely 1) Alms is a sacrifice to share in a way of giving relief 2) The precepts are the focus and care of one’s body and speech, not to hurt oneself, others and society. 3) Nekkhamma is to refrain from sins and various kinds of evil. 4) Wisdom is knowledge 5) Effort is persistence 6) Endurance is patience. Patience is the quality of being a leader in Buddhism.